Monogeneans as bioindicators: A meta-analysis of effect size of contaminant exposure toward Monogenea (Platyhelminthes) - Beric M. Gilbert (Elsevier, 2021)
Monogenea is a Class of ecologically and economically significant platyhelminth parasites of freshwater and marine hosts. Contamination of the environment has been shown to variably affect parasites resulting in alterations at the population and organismal levels. The aim of this study was to perform a meta-analysis of published data to assess similarities among responses of monogeneans to pollution and estimate effect sizes of contaminant exposure on these parasites. Effect size was calculated according to Cohen’s d based on reported mean abundance for monogeneans from individual studies. A total of 57 studies were used in the present study. Each Monogenea–contaminant record represented a single data point in the meta-analysis, and this accounted for a total of 217 useable records. Most studies were concerned with species belong to Gyrodactylidae, Diplozoidae, Ancyrocephalidae and Dactylogyridae. Assessment of the effects of specific pollutants on monogeneans have mostly been restricted to exposure to eutrophication, pulp-mill effluent and metals. Comparison of effect sizes showed strong negative effects for metals and strong positive effects for eutrophication on monogeneans. Other contaminant types had weak effect sizes on monogeneans. Comparison of effect sizes among monogenean families showed that none of the effect sizes calculated were significant but metals and disturbance contaminants showed strong negative and positive effects respectively for Gyrodactylidae. The current comparisons were based on changes in the population structure and infections of monogeneans, however, organ level effects associated with exposure to poor water quality have also been noted. In this instance, exposure has been suggested to result in asymmetry of the attachment organs of some monogeneans. Despite numerous records of impacts of pollution exposure at the population level, understanding of the physiological effects and mechanisms employed by Monogenea to survive and adapt to changes in the environment are yet to be explored. Study of these aspects would enable better understanding of the variation in the trends observed at a population level for monogeneans in relation to the quality of the macroenvironment.